PELATIHAN MEMBUAT SKENARIO DRAMA PADA KOMUNITAS YAYASAN ABAR INDONESIA - Gandadinata Thamrin; Richard Poeh; Heri Yulianto; Selvieana Indrawati; Merry Gading Mallibu (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Events held in schools and churches often use drama performances as entertainment or convey messages in the theme of the activity. This requires a story that can describe or provide a meaningful message to be conveyed to the audience present. But not everyone can make a good scenario and this is felt to be a necessity for the Abar Indonesia Foundation community where the community consists of teachers, lecturers, housewives, social workers, servants and Servants of God, as well as the general public who have a desire to learn. create a simple scenario that can be demonstrated at an event in the family, community, community, the August 17 event at the RT or RW, at school, at church or at a government office. From this need, the ABAR Indonesia Foundation asked Pelita Harapan University, Karawaci to provide an online training webinar